2009
DOI: 10.1111/j.1755-3768.2009.01534.x
|View full text |Cite
|
Sign up to set email alerts
|

β‐Defensin 1 haplotype associated with postoperative endophthalmitis

Abstract: Acta Ophthalmol. 2010: 88: 786–790 Abstract. Purpose:  Endophthalmitis is a rare but sight‐threatening complication of intraocular surgery. β‐Defensins are antimicrobial peptides that appear to be important components of the ocular immune response. We propose that variation in defensin genes may alter susceptibility to endophthalmitis. Methods:  Post‐cataract endophthalmitis patients (n = 28) and post‐cataract controls (n = 75) were recruited and DNA samples extracted. The β‐defensin 1 gene (DEFB1) was screene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The anatomical and functional prognosis is multifactorial (Carter et al. 2010) in this trauma context, with serious initial lesions such as RD ( n = 2) or choroidal haemorrhage ( n = 1).…”
Section: Discussionmentioning
confidence: 99%
“…The anatomical and functional prognosis is multifactorial (Carter et al. 2010) in this trauma context, with serious initial lesions such as RD ( n = 2) or choroidal haemorrhage ( n = 1).…”
Section: Discussionmentioning
confidence: 99%
“…DEFB1 is expressed in multiple cell types of the immune system such as macrophages, monocytes, dendritic cells, and leukocytes. More importantly, epithelial cells in many organs such as pancreas, skin, kidney, respiratory system, and digestive tract express high levels of DEFB1 [ 32 , 33 ]. Initially, DEFB1 was thought to be constitutively expressed in the body, but subsequent evidence suggested that its expression is regulated under specific conditions.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, the information regarding comparative distribution of DEFB1 polymorphisms among various populations is limited and, among admixed, HIV/AIDS patient populations from the United States, is not available. The majority of studies have been conducted in European populations (Braida et al, 2004;Ricci et al, 2009;Carter et al, 2010;Schaefer et al, 2010). Limited information is available regarding the distribution of DEFB1 polymorphisms in other populations, such as Asian (Leung et al, 2006;Chen et al, 2007;Kim et al, 2009), African (Mozambican) (Baroncelli et al, 2008), Brazilian Segat et al, 2009), American, either mixed (Jurevic et al, 2003;Ozturk et al, 2010) or Caucasian-American and Af-Am and Mexican (Prado-Montes de Oca et al, 2006).…”
Section: Discussionmentioning
confidence: 99%